NURSING CARE FOR SENSORY PERCEPTION DISORDERS: AUDITORY HALLUCINATIONS IN Mr. T WITH A FOCUS ON HARASSMENT TECHNIQUES AT THE DR. RM. SOEDJARWADI REGIONAL MENTAL HOSPITAL, KLATEN - Choeriyatun Ngatiyah; Sudiarto; Wiwik Priyatin (PT. Jurnal Center Indonesia Publisher, 2025)
Mental disorders are a health problem that remains a major challenge in Indonesia. Auditory hallucinations are a sensory perception disorder that often occurs in patients with schizophrenia. Patients have difficulty distinguishing between real and unreal stimuli, which can lead to risky behaviors such as harming themselves or others. One non-pharmacological intervention that can be applied to address hallucinations is the rebuke technique, which is a firm and directed verbal action to reject perceived hallucinations. The purpose of this study is to describe nursing care for patients with sensory perception disorders: auditory hallucinations with the application of the rebuke technique as the main intervention. This study uses a descriptive case study approach on one patient in the Flamboyan Ward of Dr. RM. Soedjarwadi Klaten Mental Hospital. Data collection was carried out through interviews, observations, and documentation studies, then analyzed based on the stages of the nursing process. The results showed that after the rebuke technique intervention was consistently implemented for three days, there was a decrease in the frequency of hallucinations from 3-4 times to 1-2 times a day. The patient also showed an increase in the ability to recognize and reject hallucinations independently. Furthermore, the patient began to engage in social interactions and participate more actively in daily activities. The conclusion is that the reprimand technique has proven effective as a nursing intervention in addressing auditory hallucinations. This intervention is simple, easy to implement, and can improve the patient's coping skills in dealing with hallucinatory symptoms.